2017
DOI: 10.1161/circoutcomes.116.003414
|View full text |Cite
|
Sign up to set email alerts
|

Direct Transport to a Percutaneous Cardiac Intervention Center and Outcomes in Patients With Out-of-Hospital Cardiac Arrest

Abstract: O ut-of-hospital cardiac arrest (OHCA) is a major public healthcare issue affecting 200 000 to 400 000 Americans each year, with large variations in incidence, resuscitation practice, and outcomes between communities.1,2 Regional systems of care involving centralization of postresuscitation care have been proposed to improve outcomes because multiple organ systems can be affected after OHCA that likely are best treated at regional centers with percutaneous cardiac intervention (PCI) and critical care capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 31 publications
1
33
0
1
Order By: Relevance
“…Using a mathematical model, Kragholm, et al concluded that there is survival benefit for cardiac arrest patients with prehospital ROSC to be transported to CAC even if journey time exceeds 20 minutes. [46] Similar findings were reported by Tranberg et al who also reported that distances from arrest location to CAC was not associated with patient survival. [43] In contrast, regression analyses from Cournoyer study stated that increasing the delay from call to hospital arrival by 14.0 min would offset the potential survival benefit of being transported to a PCI-capable centre.…”
Section: Subgroup Analyses and Sensitivity Analysessupporting
confidence: 83%
See 3 more Smart Citations
“…Using a mathematical model, Kragholm, et al concluded that there is survival benefit for cardiac arrest patients with prehospital ROSC to be transported to CAC even if journey time exceeds 20 minutes. [46] Similar findings were reported by Tranberg et al who also reported that distances from arrest location to CAC was not associated with patient survival. [43] In contrast, regression analyses from Cournoyer study stated that increasing the delay from call to hospital arrival by 14.0 min would offset the potential survival benefit of being transported to a PCI-capable centre.…”
Section: Subgroup Analyses and Sensitivity Analysessupporting
confidence: 83%
“…Survival to hospital discharge was reported in ten studies (three retrospective cohort studies and two before and after studies with adjusted analyses, and five retrospective analyses with unadjusted analyses) including 42780 patients. [38][39][40][45][46][47][48][49][50] Data from meta-analysis of 5 studies (n=11,662)…”
Section: Survival To Hospital Discharge (Critical)mentioning
confidence: 99%
See 2 more Smart Citations
“…The ACC and American Heart Association and currently recommend regionalized patient care for patients resuscitated from out‐of‐hospital cardiac arrest at hospitals that are designated as cardiac resuscitation centers. Prior studies have demonstrated that regionalization of care for cardiac arrest patients has improved outcomes, whether done at the city or state level.…”
Section: Discussionmentioning
confidence: 99%